The Role of Ethnic Parties in the Europeanization Process – the Romanian Experience - Sergiu Gherghina; George Jiglău (Romanian Journal of European Affairs, 2008)
This paper aims to show how ethnic parties can become influential actors in the process of Europeanization of post-Communist countries, by conducting a case-study of Romania. We consider Europeanization of Romania as the dependent variable of the two hypotheses we put forward. First, we test if the presence of ethnic parties in government led to an acceleration of the Europeanization process. Second, we are interested in seeing if the European dimension of ethnic parties’ political activity led to additional challenges for domestic governments in the Europeanization process. Thus, we show that the moderation of the Democratic Alliance of Hungarians in Romania (DAHR) had both positive and negative consequences for the process of Europeanization in Romania.